THE EFFECT OF THE SCHOOL ENVIRONMENT ON MATHEMATICAL LEARNING OUTCOMES IN JUNIOR HIGHT SCHOOL GORONTALO CITY STATE - La Yusran La Kalamu (International Journal of Education, Information Technology, and Others, 2018)
This study aims to find out the school environment has a direct effect on the results of mathematics learning in SMP Negeri students in Gorontalo city. This research was carried out on class VII students of the State Middle School in Gorontalo City in the odd semester of the academic year 2018/2019. The research data was obtained through tests in the form of MCQs and questionnaires. The research data was analyzed in two parts, namely descriptive analysis and inferential analysis for testing the research statistical hypothesis. The method used in this study is a survey causal path analysis model(pathanalysis).This method can be used to test the direct effect of school environment variables on the mathematics learning outcomes of Gorontalo City Public Middle School students. The population in this study were all seventh grade students of State Middle School in Gorontalo City as many as 1729 students and a total sample of 95 students. The results showed that: there was a positive direct influence of the school environment on the learning outcomes of mathematics, this showed that the more conducive the school environment would directly improve students' mathematics learning outcomes.